In vitro synergistic effects of baicalin with oxytetracycline and tetracycline against Staphylococcus aureus - Novy, Pavel; Urban, Jan; Leuner, Olga; Vadlejch, Jaroslav; Kokoska, Ladislav (The Journal of antimicrobial chemotherapy, 2011)
OBJECTIVES: In this study we examined the in vitro synergistic effect of baicalin, the flavone constituent of Scutellaria spp., in combinations with oxytetracycline and tetracycline on the growth of Staphylococcus aureus. METHODS: The MICs were determined by the broth microdilution method and the effect of combinations was evaluated according to the sum of fractional inhibitory concentration indices (FICIs). RESULTS: Synergistic activity (FICI ≤ 0.5) was observed for combinations of baicalin with oxytetracycline or tetracycline against 4 of 10 strains tested, whereas the baicalin/oxytetracycline combination possessed the strongest synergistic effect (FICI = 0.418). CONCLUSIONS: Baicalin acts synergistically with oxytetracycline and tetracycline, enhancing its antimicrobial activity against S. aureus, including methicillin- and tetracycline-resistant strains.
Keywords: Scutellaria; tetracyklin; Tetracycline; Drug Synergism; šišák; Staphylococcus aureus; lidé; flavonoidy; synergismus léků; antibakteriální látky; oxytetracyklin; Anti-Bacterial Agents; Flavonoids; Microbial Sensitivity Tests; mikrobiální testy citlivosti; Oxytetracycline; Humans